2019
DOI: 10.1136/archdischild-2019-316912
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of cord clamping at very preterm birth: outcomes at 2 years

Abstract: ObjectiveTo report outcomes at 2 years corrected age for children of women recruited to a trial comparing alternative policies for timing of cord clamping and immediate neonatal care at very preterm birth.DesignParallel group randomised (1:1) trial.SettingEight UK tertiary maternity units.ParticipantsTwo hundred and seventy-six babies born to 261 women expected to have a live birth before 32+0 weeks’ gestation.InterventionsDeferred cord clamping (≥2 min) and immediate neonatal care with cord intact or immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…One study published outcomes in early childhood for early clamping compared to delayed clamping (comparison 1) shortly after our search date and was therefore not included in the analysis. 39 Authors of this study found that delayed clamping may reduce the risk of death or adverse neurodevelopmental outcome at 2 years of age for children born ,32 weeks, but confirmation in larger studies is needed.…”
Section: Agreement and Disagreement With Previous Researchmentioning
confidence: 85%
“…One study published outcomes in early childhood for early clamping compared to delayed clamping (comparison 1) shortly after our search date and was therefore not included in the analysis. 39 Authors of this study found that delayed clamping may reduce the risk of death or adverse neurodevelopmental outcome at 2 years of age for children born ,32 weeks, but confirmation in larger studies is needed.…”
Section: Agreement and Disagreement With Previous Researchmentioning
confidence: 85%
“…Les enfants nés à moins de 32 semaines et affectés aléatoirement au groupe de CRC à 120 secondes ou plus, en comparaison avec le groupe de CIC, présentaient un moindre risque de mortalité ou de devenir neurodéveloppemental défavorable à l'âge de 2 ans (critère composite; RR : 0,61; IC à 95 % : 0,39-0,96) 13 .…”
Section: Après La Période Néonataleunclassified
“…b This statement is a compilation of 2 other WHO statements. 41,46 in infants born at 23 to 27 6 weeks' gestation who received UCM. In their systematic review, Balasubramanian et al 69 also found significantly increased risk of severe IVH (grades 3 or higher) among preterm infants ,34 weeks who received UCM compared with DCC in 4 RCTs.…”
Section: Figurementioning
confidence: 99%
“…3 RCTs revealed that DCC reduced the risks of intraventricular hemorrhage (IVH), necrotizing enterocolitis, and sepsis among preterm infants; reduced the need for blood transfusions and respiratory support; improved iron stores at 3 to 6 months; and improved neurodevelopmental outcomes at 2 years. [3][4][5][6] In a systematic review of 7 RCTs, UCM reduced the risks of IVH and oxygen requirement and improved hemoglobin levels among preterm infants. 7 However, a recent large RCT raised concerns about the risks of IVH with UCM.…”
mentioning
confidence: 99%